Epidemiology of the sarcomas of the jaws in a Peruvian population - Guevara-Canales, Janet-Ofelia (2012)
Objective: Analysis of the clinical characteristics of patients with Sarcomas of the Jaws treated in the "Instituto Nacional de Enfermedades Neoplasicas. Dr. Eduardo Caceres Graziani" from 1952-2007. Study design: Review of 155 clinical records of patients with Sarcomas of the Jaws and record of age, gender, size, location, clinical symptoms and signs, histopathological diagnoses and type of treatment. The data obtained were analyzed by means of Student's statistical t-test, Fisher and Friedman's test. Results: Analysis of 155 Sarcomas of the Jaws. The average age of patients was 36.8 years old (range: 1-80 years); the female gender was the most frequent (52.9%); the average tumor size was 5.5 cm; in upper jaw 54.84% occurred and 45.16% in the lower jaw; the predominant sign was facial asymmetry (87.74%) and the predominant symptom: pain (63.23%). The most frequent diagnosis was Osteosarcoma 50.3% followed by Chondrosarcoma 18%. Surgery plus radiation therapy was the treatment type of choice with 21.94% of cases. Conclusion: The results of this study demonstrate the delayed diagnosis and facial asymmetry and pain appear as the most important events for the diagnosis of Sarcomas of the Jaws.